Glycated serum proteins and albumin but not glycated albumin show negative correlation with BMI in an overweight/obese, diabetic population from the United States - Powers Carson, Jennifer; Arora, Jyoti (Clinical biochemistry, 2023)
•Both glycated serum proteins and albumin show weak, negative correlations with BMI.•Correlation between BMI and glycated albumin may depend upon BMI range examined.•Underlying factors for observed correlations differ in diabetics versus prediabetics.•Renal clearance of glycated and unmodified albumin may be altered with BMI increases. Multiple previously published studies have shown a weak to medium, negative correlation between BMI and glycated albumin (GA). However, many of these studies were in populations with a narrow range of BMI. It is unknown whether this trend exists if a wider BMI range is used. This is an important question for proper interpretation of GA levels in obese populations. Materials and methods: A retrospective analysis of clinical trial data (NCT02519309) was performed. After appropriate exclusions, 334 subjects remained. These included 73.7% with type 2 diabetes (T2D) diagnosis and 26.3% with prediabetes. BMI ranged from 24.8–86.9 kg/m2. Laboratory data were measured in a CLIA-certified laboratory using commercially available, automated methods. Results: No significant, negative correlation was seen between GA and BMI. However, individual components (glycated serum proteins and albumin) as well as the GA/HbA1c ratio show a weak, negative correlation with BMI for all subjects and those with T2D. The strongest negative correlation was with albumin. Examination by traditional BMI subgroups also showed statistically significant differences for those with T2D, but not for the prediabetic cohort. Correlations between BMI and C-reactive protein were similar in those with diabetes and prediabetes; however, correlation between BMI and insulin was stronger in those with diabetes. Conclusion: Negative correlations between BMI and albumin or BMI and glycated serum proteins persist in diabetic populations that are obese and overweight, even when a statistically significant negative correlation is not observed between BMI and GA. Inflammation or insulin-mediated changes in protein synthesis could be contributors to these negative correlations, but BMI-related changes to the glomerulus could also affect clearance of albumin or glycated proteins and should be examined.